Mitochondrial DNA analyses revealed low genetic diversity in the endangered Indian wild ass Equus hemionus khur. (3rd September 2017) - Khaire, Devendra; Atkulwar, Ashwin; Farah, Sameera; Baig, Mumtaz
Abstract: The Indian wild ass Equus hemionus khur, belonging to ass-like equid branch, inhabits the dry and arid desert of the Little Rann of Kutch, Gujarat. The E. h. khur is the sole survivor of Asiatic wild ass species/subspecies in South Asia. To provide first ever insights into the genetic diversity, phylogeny, and demography of the endangered Indian wild ass, we sampled 52 free-ranging individuals from the Little Rann of Kutch by using a non-invasive methodology. The sequencing of 230 bp in cytochrome b (Cyt b) and displacement loop (D-loop) region revealed that current ∼4000 extant population of Indian wild ass harbours low genetic diversity. Phylogenetic analyses confirmed that E. h. khur, E. h. onager, and E. h. kulan belong to a single strict monophyletic clade. Therefore, we suggest the delimitation of the five E. hemionus subspecies in vogue to a single species E. hemionus . The application of molecular clock confirmed that the Asiatic wild ass had undergone diversification 0.65 Million years ago. Demographic measurements assessed using a Bayesian skyline plot demonstrated decline in the maternal effective population size of the Indian wild ass during different periods; these periods coincided with the origin and rise of the Indus civilization in the northwest of the Indian subcontinent during the Neolithic. In conclusion, maintaining high genetic diversity in the existing isolated population of 4000 Indian wild asses inhabiting the wild ass sanctuary is important compared with subspecies preservation alone.